The Effect of Individualized Teach-Back Education Guided by the Roy Adaptation Model on Treatment Adherence and Coping Skills in Patients Receiving Hemodialysis: A Randomized Controlled Trial. - Acar, Elif; Eroglu, Semiha Akin (Nephrology Nursing Journal)
This randomized controlled trial evaluated the efficacy of an individualized, nurse-led, teach-back method of education intervention guided by the Roy Adaptation Model on treatment adherence and coping processes among adult patients on hemodialysis. Utilizing a parallel-group pretestposttest design, 42 outpatients were randomized into intervention (n = 21) or control (n = 21) groups. Data were collected using validated adherence and coping scales. The intervention group received three face-to-face education sessions delivered via the teach-back method. After adjusting for baseline scores, the intervention group demonstrated statistically significant and higher posttest adherence and coping scores compared with the control group. Retrospective analysis confirmed a robust post-hoc power of 0.92. This theoretically guided framework supports multidimensional treatment adherence and coping mechanisms in patients on hemodialysis.